2021
DOI: 10.3390/molecules26082204
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Enhances Inhibition Effects of Cisplatin on Cell Migration and Invasion and Tumor Growth in Breast Cancer MDA-MB-231 Cell Models In Vivo and In Vitro

Abstract: Triple-negative breast cancer (TNBC) is a refractory type of breast cancer that does not yet have clinically effective drugs. The aim of this study is to investigate the synergistic effects and mechanisms of resveratrol combined with cisplatin on human breast cancer MDA-MB-231 (MDA231) cell viability, migration, and invasion in vivo and in vitro. In vitro, MTS assays showed that resveratrol combined with cisplatin inhibits cell viability as a concentration-dependent manner, and produced synergistic effects (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…The IC 50 values for the complexes against all cell lines are listed in Table 1 . For comparison, IC 50 value for the clinical drug cisplatin was 13.95 µM for MDA-MB-231 cells at 24 h MTS assay [ 64 ]. For comparison, IC 50 value for the clinical drug cisplatin was 32.38 µM for MDA-MB-468 cells at 24 h MTT assay [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 values for the complexes against all cell lines are listed in Table 1 . For comparison, IC 50 value for the clinical drug cisplatin was 13.95 µM for MDA-MB-231 cells at 24 h MTS assay [ 64 ]. For comparison, IC 50 value for the clinical drug cisplatin was 32.38 µM for MDA-MB-468 cells at 24 h MTT assay [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, for MCF7, which showed a low degree of apoptosis after treatment with ASP, we exclude the role of cell death due to the intrinsic characteristics of the assay that allows seeding of the cells in the upper chamber, while the medium with treatment is placed only in the lower chamber. Inhibition of cell migration on MDA-MB-231 cell models has been described following treatments with traditional anticancer drugs (e.g., cisplatin) [24] and purified molecules (e.g., curcumin) [25]. Interference with cellular migration represents a pivotal effect of the anticancer activity of the extracts, suggesting a possible role in inhibition of the metastatic process.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol was also reported to enhance antitumour effects and decrease adverse effects of cisplatin in MDA‐MB‐231 xenografts and involved in the mechanism for the effect of the regulations of the JNK, PI3K/Akt, NF‐κB and ERK expressions. 200 Another study showed that the combination of sitagliptin (an antidiabetic drug) and resveratrol synergistically ameliorated clear cell renal cell carcinoma, and this effect was mediated by the decrease in TGF‐β1 and other inflammatory cytokines, such as TNF‐α, IL‐6 and STAT3. 201 In irradiated mice, HS1793 (a resveratrol analogue) reduced tumour development by activating effector T cells.…”
Section: Natural Compounds As Cancer Preventive and Therapeutic Agent...mentioning
confidence: 99%
“…A combination of resveratrol and cisplatin synergistically inhibited the MDA‐MB‐231 breast cancer cell viability and also inhibited TGF‐ß1‐induced migration and invasion of MDA‐MB‐231cells by inhibiting EMT. Resveratrol was also reported to enhance antitumour effects and decrease adverse effects of cisplatin in MDA‐MB‐231 xenografts and involved in the mechanism for the effect of the regulations of the JNK, PI3K/Akt, NF‐κB and ERK expressions 200 . Another study showed that the combination of sitagliptin (an antidiabetic drug) and resveratrol synergistically ameliorated clear cell renal cell carcinoma, and this effect was mediated by the decrease in TGF‐ß1 and other inflammatory cytokines, such as TNF‐α, IL‐6 and STAT3 201 .…”
Section: Natural Compounds As Cancer Preventive and Therapeutic Agent...mentioning
confidence: 99%